Digital Student Worksheets to Improving Students' Learning Independence - Juliana , Netty; Ampera, Dina; Farihah; Baharuddin; Sinukaban, Veronika Yulisna (Universitas Pendidikan Ganesha, 2024)
The independent campus learning curriculum currently being developed focuses on student-centered learning so that lecturers are not the only source of learning. This research was motivated by the lack of student learning independence and low learning outcomes in craft arts learning. The aim of the research is to produce Digital Student Worksheets that are feasible and effective in increasing student learning independence in Arts and Crafts courses in the Fashion Design Education study program. This development research uses the Thiagarajan 4-D development model. This model consists of 4 stages, including the needs analysis stage, product design stage, validation and evaluation stage. The results of validation by material experts obtained an average result of 4.12 in the feasible category. the validation results from media experts obtained an average score of 4.27 in the adequate category. The results of trials carried out by lecturers and students obtained an average score of 4.55 in the very good category. At this stage, an evaluation of all activities that have been carried out is carried out, especially the input provided by experts and users. The results of the posttest carried out obtained an increase of 28% in improving learning outcomes. Digital LKM is suitable for use in learning and motivates students to increase student independence. Digital LKM can help students learn independently. The implication of this research is that digital LKM can be used by teachers because it can present problems in more detail so that students can construct their knowledge independently.